Absorbance thickness in the formation of biofilm produced by Candida albicans due to glucose, lactose, protein (soy) and iron induction - Indah Listiana Kriswandini (Ektodermal Displazi Grubu, 2019)
Candida albicans (C. albicans) is a major cause of Candidiasis in the oral cavity. Carbohydrates and protein are required by the fungI to grow when it is infecting the soft tissues of the oral cavity. Whereas in Candidiasis therapy, reducing the carbohydrate diet and increasing intake of iron and vitamins must be done to inhibit the growth of C. albicans in the soft tissue of the oral cavity. The aim of this study to determine the thickness of absorbance in the formation of biofilm from C. albicans induced by various materials such as Glucose, Lactose, Protein (Soy) and Iron. The experimental study grow C. albicans on Saboraud Dextrose Agar with 4 types of treatment as follow group A, the C. albicans is induced by 5% Glucose, group B is induced by 5% lactose, group C is induced by soy protein and group D is induced by Iron (5% FeCl2). Whereas group E is the growth control of C. albicans without any induction. Each treatment was replicated with 6 times, then stained with Crystal Violet. A microplate assay was used to carry out tests. The average of Optical Density (OD) is read with a wavelength of 492 each group as follow A = 0.197; B = 0.279; C = 0.297; D = 0.177 and E = 0.053. C. albicans biofilm induced by protein and lactose materials had much thicker OD than induced by glucose and iron. The conclusion of this study that the thickness of absorbance in the formation of C. albicans biofilms is influenced by the demand of the growth factors of C. albicans.